Lettering, Asian Building - Ghosh, Ayan (2023)
Asian Building on R Kamani Road houses offices of Life Insurance Corporation, New India Assurance Company, and Milton Housewares Private Limited, among other companies. The building was completed in 1932 and has some influence from Art Deco, including the bold lettering used over the cantilevered porch at the entrance.